2008
DOI: 10.1242/jeb.009597
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of Cnidarian bleaching: stress causes the collapse of symbiosis

Abstract: SummaryCnidarian bleaching is a breakdown in the mutualistic symbiosis between host Cnidarians, such as reef building corals, and their unicellular photosynthetic dinoflagellate symbionts. Bleaching is caused by a variety of environmental stressors, most notably elevated temperatures associated with global climate change in conjunction with high solar radiation, and it is a major contributor to coral death and reef degradation. This review examines the underlying cellular events that lead to symbiosis dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
980
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 789 publications
(1,050 citation statements)
references
References 66 publications
21
980
2
3
Order By: Relevance
“…The exact biochemical sequence triggering the caspase cascade in the host remains elusive; however, based on studies in metazoan models (41), we suggest that the ROS produced by the algal symbionts compromise the structural integrity of mitochondrial membrane in the host cells, thereby stimulating the release of factors initiating a caspase cascade. In the case of sensitive corals, it is most likely that ROS levels will continue to accumulate after bleaching as a result of mitochondrial dysfunction and further evoke the apoptotic machinery (6,33,42).…”
Section: Discussionmentioning
confidence: 99%
“…The exact biochemical sequence triggering the caspase cascade in the host remains elusive; however, based on studies in metazoan models (41), we suggest that the ROS produced by the algal symbionts compromise the structural integrity of mitochondrial membrane in the host cells, thereby stimulating the release of factors initiating a caspase cascade. In the case of sensitive corals, it is most likely that ROS levels will continue to accumulate after bleaching as a result of mitochondrial dysfunction and further evoke the apoptotic machinery (6,33,42).…”
Section: Discussionmentioning
confidence: 99%
“…The studies suggested that host cell death can contribute to subsequent symbiont cell mortality, a process that appears similar to a host innate immune response. The results indicated that no single pathway is responsible for symbiont release during bleaching, allowing to formulate a model for cellular processes involved in the control of cnidarian bleaching where apoptosis and autophagy act together in a see-saw mechanism such that if one is inhibited the other is induced (Dunn et al 2007;Weis 2008;Paxton et al 2013).…”
Section: Autophagy Induced By Environmental Stress On Aquatic Invertementioning
confidence: 99%
“…In corals, apoptosis has been observed in response to hyperthermic oxidative stress, disease, and as a postphagocytic removal mechanism of zooxanthellae during the onset of symbiosis (10,12). The recent Acropora digitfera genome suggests that coral possess homologs to the human intrinsic and extrinsic apoptotic pathways (13).…”
Section: Significancementioning
confidence: 99%